2010
DOI: 10.1111/j.1740-8784.2009.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Exchanges in China: Organizational Forms and Governance Mechanisms

Abstract: This article discusses how organizations exchange with one another in China, focusing on the type of organizational ownership and the form of governance mechanism. The theoretical foundation builds on institutional theory, resource dependence theory, agency theory, and evolutionary theory. Given the three main forms of organizations in China – state‐owned enterprises, privately owned enterprises, and foreign‐invested enterprises – we show how these organizations choose between two types of governance mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 66 publications
(148 reference statements)
1
57
0
Order By: Relevance
“…The present article suggests that Zhang and Keh (2010)'s research provides theoretical support for the proposition that SOEs are dominated by Feudal Hierarchy culture. And their three lines of arguments can also be considered as reasons for the stagnation of Feudal Hierarchy culture in SOEs: firstly, SOEs possess policy advantage and monopoly positions and thus lack market competition pressures; secondly, serious agency problems and deficient supervision undermine SOEs' drive for improving efficiency; finally, the relatively long organization histories may bring higher culture inertia to SOEs compared with POEs in China.…”
Section: A Review On Zhang and Keh (2010)'s Researchmentioning
confidence: 51%
See 1 more Smart Citation
“…The present article suggests that Zhang and Keh (2010)'s research provides theoretical support for the proposition that SOEs are dominated by Feudal Hierarchy culture. And their three lines of arguments can also be considered as reasons for the stagnation of Feudal Hierarchy culture in SOEs: firstly, SOEs possess policy advantage and monopoly positions and thus lack market competition pressures; secondly, serious agency problems and deficient supervision undermine SOEs' drive for improving efficiency; finally, the relatively long organization histories may bring higher culture inertia to SOEs compared with POEs in China.…”
Section: A Review On Zhang and Keh (2010)'s Researchmentioning
confidence: 51%
“…In specific, Bureaucratic Hierarchy corresponds to contractual governance which relies on formal rules and procedures, and Feudal Hierarchy corresponds to guanxi governance which counts on informal processes. Zhang and Keh (2010) analyzed the characteristics of SOEs based on the resource dependence theory, agency theory, and evolutionary theory. They made the proposition that SOEs used both guanxi and contracts with the former playing a more important role, because of the following three lines of arguments:…”
Section: A Review On Zhang and Keh (2010)'s Researchmentioning
confidence: 99%
“…Sociologists have demonstrated that trust and other forms of social relationships play crucial role in economic transactions (Zheng et al, 2008). Social control has been recently considered as useful tool that can be used to inhibit opportunism, enhance cooperation in buyer -supplier exchanges (Kim et al, 2010;Liu et al, 2010), and reduce transaction cost in terms of monitoring and negotiations (Zhang & Keh,, 2009;Cai et al, 2009). …”
Section: Social Control and Sc Performancementioning
confidence: 99%
“…For example outsourcing, as operational function of SC, is characterized by quality, delivery and cost related risks, whose management requires development of long-term relationship among chain parties (Haung et al, 2014). Prior studies have indicated that in spite of the advantages of long-term relationships between SC parties, (suppliers and manufacturers, say), opportunistic behaviour and power conflicts among the parties could damage network collaboration and negatively affect performances (Claro et al, 2010;Zhang & Keh, 2009;Prajogo & Olhager, 2012;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, guanxi can be perceived as an organisational resource if it is utilised for the purpose of the organisational goal achievement or as a way of finding business solutions (Xin and Pearce 1996;Yeung and Tung 1996;Luo 1997a;Fock and Woo 1998;Tsang 1998;Park and Luo 2001;Gu, Hung, and Tse 2008;Standifird 2006). Guanxi can also be considered to be an organisational strategic resource (Peng and Heath 1996;Luo 1997aLuo , 1997bLuo and Chen 1997;Zhang and Keh 2010). Furthermore, resource heterogeneity and imperfect mobility represent two core elements of the RBV theory (Barney 1991).…”
Section: The Literaturementioning
confidence: 99%